Peran Efikasi Diri, Motivasi dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa - Effendi, Nur Ika; Nelvia, Risni; Winneh, Sri; Suliska, Gita; Anjaya, Ade Tribuana; Husna, Fitria (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
The spirit of entrepreneurship as early as possible needs to be implemented in Indonesia considering that interest in entrepreneurship is still very low. Students should prepare to start a business, not look for a company, including the largest number of students at the Faculty of Economics, Muara Bungo University. This research wants to know the influence of self-efficacy, motivation, and family environment on interest in entrepreneurship. The data collection technique for this research uses a questionnaire with a sample size of 150 respondents and the sampling technique is simple random sampling. Based on data processing with Smart PLS 3.0 was found that only motivation and family environment had a significant influence on interest in entrepreneurship, but the three variables influenced students' interest in entrepreneurship by 0.592 in the moderate category. It's hoped that economic Faculty students at Muara Bungo University will be able to develop entrepreneurial interests that can create jobs